Perfectionism and depressive symptoms: The effects of psychological detachment from work. (1st October 2017) - Gluschkoff, Kia; Elovainio, Marko; Hintsanen, Mirka; Mullola, Sari; Pulkki-Råback, Laura; Keltikangas-Järvinen, Liisa; Hintsa, Taina
Abstract: We examined the association of perfectionism with depressive symptoms and tested whether psychological detachment from work would both mediate and moderate the association. The participants were 76 primary school teachers (87% female) who responded to measures of perfectionism (Multidimensional Inventory on Perfectionism in Sports adapted for teachers), psychological detachment from work (The Recovery Experience Questionnaire), and depressive symptoms (Beck Depression Inventory-II). Perfectionism comprised both adaptive and maladaptive dimensions. Adaptive perfectionism referred to striving for perfection, whereas maladaptive perfectionism involved negative reactions to imperfection and perceived pressure to be perfect. According to our results, negative reactions to imperfection were associated with higher depressive symptoms, and lower level of psychological detachment from work played a minor mediating role in the association. There was, however, no association between negative reactions to imperfection and higher depressive symptoms when detachment from work was high. Our findings suggest that striving for perfection and perceived pressure to be perfect might not contribute to depressive symptoms in teaching. Instead, teachers experiencing negative reactions to imperfection and low psychological detachment from work could be at risk for developing depressive symptoms. Finding ways to psychologically detach from work may benefit teachers characterized by negative reactions to imperfection. Highlights: Negative reactions to imperfection were associated with higher depressive symptoms. Psychological detachment from work played a minor mediating role in the association. The association completely attenuated when detachment from work was high.